Not-Not as Another Spatial Logic of Constitutive Negation - Masamichi Tamura (Footprint)
The article introduces Japanese architect Hiroshi Hara (1936–) and his creative criticism against unilateral globalisation　in the 1970–80s as a unique legacy of pioneering cosmotechnical criticism in Japan. The growing vocabulary of cosmotechnics has offered opportunities to revisit the legacies of alternative perspectives to architecture, urbanisation and technology and thereby redefine the role of architecture as a major world-making agency in the Anthropocene. Joining such efforts, the present review examines Hara’s 1987 book Space <From Function to Modality> (1987), which collects six interconnected essays written in 1975–1987, focusing especially on ‘On Homogenous Space’ in 1975 and ‘From Function To Modality’ and ‘Not-Not and a Spatial Tradition of Japan’ both in 1987 to trace the trajectory of his three main concepts ‘function,’ ‘homogenous space’ and ‘modality.” Following how he appropriates of Heideggerian ‘tool’ as its pivot and articulates a constitutive negation called Not-Not, this review contextualises its relevance in contemporary cosmotechnical criticism initiated by Yuk Hui, through their respective reinvestigations into geometrical space and Eastern traditions of constitutive negation. The article concludes by highlighting Hara’s non-essentialist approach to avoid the East-West axis and decentralise globalisation from beyond his own horizon in Japan.